Factors associated with the use of anesthetic drug infusion in patients with status epilepticus and their relation to outcome: a prospective study - Shamloul, Reham; El-Tamawy, Mohamed; Amer, Hanan; Kishk, Nirmeen; Shaker, Ehab; Nawito, Amani; Basheer, Mye; Alieldin, Nelly; Othman, Alshimaa; Talaat, Lobna (Acta neurologica Belgica, 2022)
Status epilepticus (SE) is one of the most dreadful neurological emergencies; unfortunately, studies targeting SE are still inadequate. This study aims to identify factors associated with the use of CIVAD in patients presenting with status epilepticus and detect those impact the clinical outcome. A prospective study involving 144 episodes of SE in 144 patients. Patients were categorized according to whether or not they received CIVAD. Subjects underwent clinical assessment, brain imaging, and EEG. The consciousness level was assessed using the Glasgow coma scale (GCS) and the Full outline of responsiveness (FOUR) scale. SE severity score (STESS) and Epidemiology-based mortality score (EMSE) were used as scales for outcome prediction. Continuous IV anesthetic drug infusion was initiated in 36% of patients (+ CIVAD). Such groups showed a significantly worse initial level of consciousness (< 0.001), an unstable course of seizure evolution (0.009), and all of them showed abnormal EEG patterns. A significantly higher number of patients (+ CIVAD) developed complications (< 0.001), had higher outcome prediction scores (< 0.001), and mortality rates (< 0.001) compared to those who did not need CIVAD (− CIVAD). Mortality was associated with acute symptomatic etiology and higher total doses of propofol. Among the study population, mortality among patients who received CIVAD was associated with acute symptomatic SE and prolonged propofol infusion rather than any clinical parameters or predictor scores.